2016
DOI: 10.4171/ifb/349
|View full text |Cite
|
Sign up to set email alerts
|

A mixed formulation of the Stefan problem with surface tension

Abstract: A dual formulation and finite element method is proposed and analyzed for simulating the Stefan problem with surface tension. The method uses a mixed form of the heat equation in the solid and liquid (bulk) domains, and imposes a weak formulation of the interface motion law (on the solidliquid interface) as a constraint. The basic unknowns are the heat fluxes and temperatures in the bulk, and the velocity and temperature on the interface. The formulation, as well as its discretization, is viewed as a saddle po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…The formulation (4.16) was shown to be well-posed, by verifying coercivity and inf-sup conditions [10,12], in our previous work [16] with the chosen norms (4.14), (4.15). Furthermore, we showed that the semi-discrete system (4.5), (4.6) satisfies both an a priori stability bound in time and a conservation law [16].…”
Section: Variational Formulation 45 Findmentioning
confidence: 83%
See 4 more Smart Citations
“…The formulation (4.16) was shown to be well-posed, by verifying coercivity and inf-sup conditions [10,12], in our previous work [16] with the chosen norms (4.14), (4.15). Furthermore, we showed that the semi-discrete system (4.5), (4.6) satisfies both an a priori stability bound in time and a conservation law [16].…”
Section: Variational Formulation 45 Findmentioning
confidence: 83%
“…interface motion law appears as a constraint in the system of equations with a balancing Lagrange multiplier that represents the interface temperature. Our work recently appeared in [16], where we showed that our method satisfies an a priori energy bound for the time semi-discrete and fully discrete cases. It also satisfies a conservation law for the thermal energy.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations